2005
DOI: 10.1177/183693910503000106
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Preservice Teachers in the Preschool Setting: Perceptions of the role

Abstract: The success of professional experience for preschool preservice teacher learning is valued and based very much on the relationship developed between all stakeholders. What motivates the preschool-based teachers and how they see their role in this relationship is integral to achieving effective outcomes for both themselves and the preservice teachers. Recent data collected from preschool teachers has identified their perceptions of what participating in the preservice relationship adds to their personal and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 10 publications
(20 reference statements)
2
44
0
Order By: Relevance
“…Teachers who are considered experienced in the classroom, and have chosen not to participate in the program, did not necessarily see themselves as having the required expertise to mentor a preservice teacher. Comments from Walkington's (2005) research demonstrate the perceptions.…”
Section: Reluctance To Participatementioning
confidence: 82%
See 4 more Smart Citations
“…Teachers who are considered experienced in the classroom, and have chosen not to participate in the program, did not necessarily see themselves as having the required expertise to mentor a preservice teacher. Comments from Walkington's (2005) research demonstrate the perceptions.…”
Section: Reluctance To Participatementioning
confidence: 82%
“…Australian research focused on the benefits and risks of mentoring a preservice teacher has revealed practical insights into what influences teachers' decisions to participate (Sinclair et al, 2005;Walkington, 2005). The benefits of mentoring have been well documented in existing literature and these were affirmed in the Australian research.…”
Section: Reluctance To Participatementioning
confidence: 83%
See 3 more Smart Citations